Identity and Access Management for Libraries - Jin, Qiang; Kudeki, Deren (Qualitative and Quantitative Methods in Libraries; Vol 6 No 3 (2017): September 2017 Issue, 2019)
Linked open data will change libraries in a dramatic way. It will redesign metadata, and display metadata on the web. In order to prepare for linked open data, libraries will gradually transition from authority control creating text strings to identity and access management using identifiers to select a single identity. The key step for moving into the linked open data for identity and access management for libraries is to correct thousands of incorrect names and subject access points in our online catalogs. This article describes a case study of the process of cleaning up unauthorized access points for personal and corporate names in the University of Illinois Library online catalog. The authors hope that this article will help readers of other libraries prepare for linked open data environment.